THE INFLUENCE OF TIME MANAGEMENT ON THE QUALITY OF ROAD CONSTRUCTION PROJECTS IN OLAYAMA VILLAGE, HURUNA DISTRICT, SOUTH NIAS REGENCY - Setiaman Halawa; Sophia Molinda Kakisina; Martha Surya Dinata Mendrofa; Heniwati Gulo (Jurnal Ilmiah METADATA, 2026)
This research was conducted on a road construction project in Olayama Village, Huruna District, South Nias Regency with the aim of determining the effect of time management on the quality of the road construction project and how big the influence is. This research uses a quantitative approach with data collection techniques, namely observation and distribution of questionnaires to 30 respondents who are residents of Olayama Village. The results of the study show that the results of the simple linear regression analysis show the equation Y = 21.518 + 0.405X. meaning that time management has a positive effect on project quality. Meanwhile, the t-test results obtained a t-count value of 2.999> t-table 1.701 with a significance of 0.006 <0.05. This proves that time management has a significant effect on project quality. Meanwhile, the magnitude of the influence is shown from the results of the determination test, which is 0.393 or 39.3%. This shows that the time management variable has a positive and significant effect on the quality of road construction projects in Olayama Village, Huruna District, South Nias Regency, meaning that Ho is rejected and Ha is accepted.